BMSC-Derived ApoEVs Promote Craniofacial Bone Repair via ROS/JNK Signaling. (June 2022) - Li, M.; Xing, X.; Huang, H.; Liang, C.; Gao, X.; Tang, Q.; Xu, X.; Yang, J.; Liao, L.; Tian, W.
Bone defect caused by trauma, neoplasia, congenital defects, or periodontal disease is a major cause of disability and physical limitation. The transplantation of bone marrow mesenchymal stem cells (BMSCs) promotes bone repair and regeneration. However, it has been shown that most BMSCs die within a short period after transplantation. During apoptosis, BMSCs generate a large number of apoptotic cell–derived extracellular vesicles (ApoEVs). This study aims to understand the potential role of ApoEVs in craniofacial bone defect repair and regeneration. First, we confirmed that BMSCs undergo apoptosis within 2 d after transplantation into the defect of the cranium. Abundant ApoEVs were generated from apoptotic BMSCs. Uptake of ApoEVs efficiently promoted the proliferation, migration, and osteogenic differentiation of recipient BMSCs in vitro. ApoEVs from cells in the middle stage of apoptosis were the most efficient to enhance the regenerative capacity of BMSCs. Moreover, a critical size bone defect model in rats was used to evaluate the osteogenic property of ApoEVs in vivo. Local transplantation of ApoEVs promoted bone regeneration in the calvarial defect. Mechanistically, ApoEVs promoted new bone formation by increasing intracellular reactive oxygen species to activate JNK signaling. This study reveals a previously unknown role of the dying transplanted BMSCs in promoting the viability of endogenous BMSCs and repairing the calvarial defects. Since it could avoid several adverse effects and limits of BMSC cytotherapy, treatment of ApoEVs might be a promising strategy in craniofacial bone repair and regeneration.